Pengembangan Modul Bimbingan dan Konseling untuk Pencegahan Perilaku Seksual Pranikah Siswa Sekolah Menengah Atas (SMA) - Pane, Riem Malini; Mudjiran, Mudjiran; Daharnis, Daharnis (Universitas Negeri Padang, 2014)
The aims of the research were: (1) producing prevention module of premarital sexual behavior on Senior High School students who were proper according to the experts in order to be used by guidance and counseling teachers/counselors, (2) describing the function of the module to prevent the students from premarital sexual behavior. This research was a development research which was conducted by using ADDIE model (Analyze, Design, Development, Implementation, and Evaluation). Research subjects consisted of three experts and twenty three guidance and counseling teachers/counselors. The result of the research shown that the module, the research product, is appropriate to be used to prevent the students from premarital sexual behavior and can be used by the students as well as the guidance and counseling teachers/counselors in preventing the students from premarital sexual behavior.